Clinical outcome for heart failure hospitalizations in patients with leadless pacemaker. Issue 5 (28th July 2022) - Katsuki, Tomonori; Nagashima, Michio; Kono, Hiroyuki; Sadohara, Yohei; Hirokami, Jun; Kuji, Rei; Korai, Kengo; Fukunaga, Masato; Hiroshima, Kenichi; Ando, Kenji
Abstract: Introduction: The long‐term performance of leadless pacemaker (LPM) has not been well evaluated. Methods: Between September 2017 and January 2021, 929 consecutive patients who underwent pacemaker implantation were grouped according to the types of pacemakers: LPM (LPM group, n  = 368) and conventional pacemaker (PM group, n  = 561). Results: The median follow‐up duration was 1.7 years (interquartile range 0.8–2.6 years). Hospitalization rate for heart failure in the LPM group was 9.3%, 15.6%, and 21.6% at 1, 2, 3 years, respectively. The LPM group had a significantly higher adjusted heart failure hospitalization risk than the PM group [hazard ratio (HR) 1.70, 95% confidence interval (CI) 1.09–2.64, p  = .01]. More patients with symptomatic bradycardia caused by sinus node dysfunction (SND) in the LPM group ( n  = 150) were admitted to the hospital for heart failure compared to those in the PM group ( n  = 219) (HR 2.02, 95%CI 1.04–3.90, p  = .03), whereas no significant difference was observed between the two groups in the patients with bradycardia caused by atrial fibrillation (LPM group, n  = 71; PM group, n  = 18) or atrioventricular block (LPM group, n  = 147; PM group, n  = 324). Conclusions: Patients who received LPM implantation had greater hospitalization risk for heart failure, compared to those who received conventional pacemaker implantation. The increased risk was mainly attributed to patients with SND.